2019
DOI: 10.1038/s41420-019-0151-0
|View full text |Cite
|
Sign up to set email alerts
|

Maturation-associated gene expression profiles during normal human bone marrow erythropoiesis

Abstract: Erythropoiesis has been extensively studied using in vitro and in vivo animal models. Despite this, there is still limited data about the gene expression profiles (GEP) of primary (ex vivo) normal human bone marrow (BM) erythroid maturation. We investigated the GEP of nucleated red blood cell (NRBC) precursors during normal human BM erythropoiesis. Three maturation-associated populations of NRBC were identified and purified from (fresh) normal human BM by flow cytometry and the GEP of each purified cell popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 55 publications
1
29
0
1
Order By: Relevance
“…GPX4 was highly expressed in our culture system of human erythroid differentiation, reaching a peak at day 6 that corresponds to erythroblast exponential amplification associated with higher transferrin receptor expression and the beginning of hemoglobin synthesis. [49][50][51] Because erythroblasts require a high bioavailable iron concentration to synthesize hemoglobin, a seducing hypothesis would be that GPX4 would protect these cells with an elevated cellular iron pool from ferroptosis. However, no significant impact of GPX4 inhibition in terms of cell death was observed during erythroblast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…GPX4 was highly expressed in our culture system of human erythroid differentiation, reaching a peak at day 6 that corresponds to erythroblast exponential amplification associated with higher transferrin receptor expression and the beginning of hemoglobin synthesis. [49][50][51] Because erythroblasts require a high bioavailable iron concentration to synthesize hemoglobin, a seducing hypothesis would be that GPX4 would protect these cells with an elevated cellular iron pool from ferroptosis. However, no significant impact of GPX4 inhibition in terms of cell death was observed during erythroblast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Erythropoiesis occurs from pluripotent stem cells in the bone marrow, with the erythroid progenitor being BFU-E (erythroid explosion-forming unit), which results in colony-forming units (CFU-E), mature erythroid precursors, reticulocytes, and red blood cells [ 126 ]. Erythroid differentiation and maturation occur in erythroblastic islands, and these complex events of proliferation, differentiation, and maturation depend on several factors, such as GATA-binding protein 1 and 2 (GATA 1 and 2), SCF, IGF (insulin-like growth factor), BPA (erythroid burst-promoting activity), IL-3, and EPO (erythropoietin) [ 127 , 128 , 129 , 130 ], in addition to nutritional aspects, like iron, folate, and B12 vitamin [ 131 ]. Yet, the influence of Mg 2+ on the erythropoiesis process in the bone marrow is not clear.…”
Section: The Role Of Mg 2+ In Hematopoiesismentioning
confidence: 99%
“…A genome-wide expression study of skeletal muscle biopsies from upper gastro-intestinal cancer patients highlighted ALAS1 as downregulated in patients with cancer cachexia [27]. ALAS2 and ALAS1 encode the same enzyme, 5′-Aminolevuilnnate Synthetase, which plays a key role in heme synthesis [28]. Previous studies have demonstrated that ALAS1 and ALAS2 expression levels are increased during erythropoiesis in healthy individuals [28].…”
Section: Discussionmentioning
confidence: 99%
“…ALAS2 and ALAS1 encode the same enzyme, 5′-Aminolevuilnnate Synthetase, which plays a key role in heme synthesis [28]. Previous studies have demonstrated that ALAS1 and ALAS2 expression levels are increased during erythropoiesis in healthy individuals [28]. ALAS2 is erythroid-specific whereas ALAS1 is expressed in many tissues, including skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation